Sympathetic Ophthalmia in Pediatric Age Group: Clinical Features and Challenges in Management in a Tertiary Center in Southern India. (October 2014) - Kumar, Kshitiz; Mathai, Annie; Murthy, Somasheila I.; Jalali, Subhadra; Sangwan, Virender; Reddy Pappuru, Rajeev; Pathangay, Avinash
Abstract Purpose: To study the clinical features and visual outcome of sympathetic ophthalmia in pediatric patients attending a tertiary care center. Methods: Retrospective review of patients ≤16 years with sympathetic ophthalmia seen during the period 2001–2011. Results: During this period, 2511 pediatric patients with open globe injuries and 14 patients with sympathetic ophthalmia were seen. Six patients developed sympathetic ophthalmia during follow-up here. The incidence rate of sympathetic ophthalmia is 0.24% (6/2511, 95% CI:0.05–0.43%). The commonest presenting signs were anterior uveitis and exudative detachment. All patients were treated with systemic steroids, while 7 patients received additional immunosuppressive therapy. Eight patients had a follow-up of more than 6 months. Mean presenting best-corrected visual acuity (1.25 ± 1.03 logMAR) in the sympathizing eye improved significant following treatment (0.42 ± 0.80 logMAR, p = 0.003). Conclusions: The incidence of sympathetic ophthalmia was 0.24%. Appropriate immunosuppression can lead to favorable visual outcomes in the sympathizing eye.